ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MATA PELAJARAN ALGORITMA STANDAR DENGAN MENGGUNAKAN SCRATCH ( Studi Kasus Di Kelas X SMK Negeri 5 Kupang ) - Sergius Erdin Mowata; Maria Magdalena Beatrice Sogen; Khatrin Juliani Taku Neno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sergius Erdin Mowata, 2026. Analysis of Students' Creative Thinking Skills in the Standard Algorithm Subject Using Scratch (A Case Study of Tenth-Grade Students at SMK Negeri 5 Kupang). Supervised by Dr. Maria M.B. Sogen, S.Kom., M.Pd. and Khatrin J. Taku Neno, S.Pd. Kom., M.Pd. Informatics Education Study Program, Faculty of Teacher Training and Education, Universitas Citra Bangsa Kupang. This study was motivated by the varying levels of students' creative thinking skills in learning Standard Algorithms using Scratch. Based on preliminary observations and interviews, it was found that some students still experienced difficulties in generating original ideas, applying various problem-solving strategies, and elaborating programming projects in detail. These conditions indicate the need for an in-depth investigation of students' creative thinking processes in completing Scratch-based programming projects. This study aims to analyze students' creative thinking skills, identify the strategies they use to overcome programming difficulties, and identify the challenges faced by teachers in teaching Standard Algorithms using Scratch. This study employs a qualitative approach with a case study method. Data were collected through structured observations, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman interactive analysis model, which consists of data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through triangulation techniques. The findings of this study are expected to provide a comprehensive description of students' creative thinking skills based on the indicators of fluency, flexibility, originality, and elaboration, and to serve as a reference for teachers in designing more effective, creative, and student-centered Informatics learning strategies to enhance students' creative thinking skills in learning Standard Algorithms using Scratch.